2008
DOI: 10.1111/j.1365-2559.2008.03183.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking‐related changes in the background lung of specimens resected for lung cancer: a semiquantitative study with correlation to postoperative course

Abstract: AEF is an important smoking-related change in the lung that appears to correlate with the smoking history, and its distinction from UIP/P may be important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
136
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(147 citation statements)
references
References 25 publications
9
136
0
2
Order By: Relevance
“…All tumors were classified according to standard histopathological criteria. 44 Histological evaluation of the frozen tumor tissues showed that on average, all specimens studied consisted of 68% ± 15% tumor cells. Adjacent non-neoplastic tissues were used as control tissues for the expression studies.…”
Section: Methodsmentioning
confidence: 99%
“…All tumors were classified according to standard histopathological criteria. 44 Histological evaluation of the frozen tumor tissues showed that on average, all specimens studied consisted of 68% ± 15% tumor cells. Adjacent non-neoplastic tissues were used as control tissues for the expression studies.…”
Section: Methodsmentioning
confidence: 99%
“…(45) encontraron que el 70% de los pacientes que desarrollaron síndrome de dificultad respiratoria poslobectomía (por cáncer de pulmón) presentaron patrón histológico de combinación de fibrosis pulmonar y enfisema. Otros trabajos describen mayor incidencia de falla respiratoria y reintubación en estos pacientes (17%) (46).…”
Section: Pronósticounclassified
“…9 However, studies based on lung cancer resection specimens have shown that fine fibrosis in the alveolar walls around respiratory bronchioles is in fact very common in the lungs of cigarette smokers who have no clinical evidence of an ILD. 2,3,5 Further, Wright et al 10 found that, in fact, in most smokers fibrosis in the walls of bronchioles actually correlates with physiologic abnormalities of airflow obstruction rather than with the restrictive profile typical of most ILDs. Thus, the extent of fibrosis in or around the bronchiolar wall does not appear to be a useful criterion for separating RB and RBILD, and most authors make the distinction on the presence or absence of clinical features of an ILD.…”
Section: Respiratory Bronchiolitis and Rbildmentioning
confidence: 99%
“…This lesion has been referred to by various names, including respiratory bronchiolitis-interstitial lung disease with fibrosis, 1 airspace enlargement with fibrosis, 2 and smoking-related interstitial fibrosis. 3 We have suggested that, to avoid confusion with other forms of smoking-related interstitial lung disease (ILD), the lesion be referred to as respiratory bronchiolitis with fibrosis (RBF).…”
mentioning
confidence: 99%